Cooperação na fronteira entre Brasil e Uruguai: o caso dos cursos técnicos binacionais - Amorim, Márcio Estrela de (2021)
The present thesis is about regional integration policies at national borders and, more specifically, the cooperation between Brazil and Uruguay in the area of professional education. For this case study, the institutional partnership established between the Federal Institute of Education, Science and Technology of Rio Grande do Sul and the Council Of Professional Technical Education of Uruguay. As a general objective, we aim to contribute to understanding of regional integration policies of borders and, in this way, we defined four specific objectives: i) recognize the social representation, elaborated by the local actors, on the border between Santana do Livramento and Rivera; ii) to check if the border interaction environment configures as a spatial support for the construction of an identity specific to that territory; iii) to understand the institution process of the binational policy of professional education between Brazil and Uruguay, and iv) to identify the constitutive elements of binationality as a formative proposal and the institutional effectiveness in its promotion. Based on the studies of Geography, as well different areas of Social Sciences, we establish the frontier as a structural concept and the territory as a concept articulator, so then, we can apply the concept of territoriality in a triad that supports the relationships we propose. As for the method, we perceive it was guided for the Complex Thought, in which we operate an eminently qualitative analysis, focused through a case study, which were analytical tools through the Social Representation Theory and textual Analysis Discoursive. Through the articulation of different instruments, techniques and methodologies, we had access to phenomenon and representations that relate to the particular way of understanding and communicating of the interlocutors this study and, therefore, they express the specific nature of the universe to which they belong and result. However, based on experience, empirical observation, the crossing between the data produced and the attentive and thorough record of all the operated choices and procedures, it was possible to carry out an analysis that allows establishing a relationship between the internal and external logic of that territory, conceiving an organization capable of contextualizing and globalizing what is unique.